Chemical Composition of Lipophilic Compounds From Rice (Oryza sativa) Straw: An Attractive Feedstock for Obtaining Valuable Phytochemicals - Rosado, Mario J.; Marques, Gisela; Rencoret, Jorge; Gutiérrez, Ana; del Río, José C. (Frontiers in Plant Science, 2022)
Rice (Oryza sativa L.) straw is a highly abundant, widely available, and low cost agricultural waste that can be used as a source to extract valuable phytochemicals of industrial interest. Hence, in the present work, the chemical composition of the lipophilic compounds present in rice straw was thoroughly characterized by gas chromatography and mass spectrometry using medium-length high-temperature capillary columns, which allowed the identification of a wide range of lipophilic compounds, from low molecular weight fatty acids to high molecular weight sterols esters, sterol glucosides, or triglycerides in the same chromatogram. The most abundant lipophilic compounds in rice straw were fatty acids, which accounted for up to 6,400 mg/kg (41.0% of all identified compounds), followed by free sterols (1,600 mg/kg; 10.2%), sterol glucosides (1,380 mg/kg; 8.8%), fatty alcohols (1,150 mg/kg; 7.4%), and triglycerides (1,140 mg/kg; 7.3%), along with lower amounts of high molecular weight wax esters (900 mg/kg; 5.8%), steroid ketones (900 mg/kg; 5.8%), monoglycerides (600 mg/kg; 3.8%), alkanes (400 mg/kg; 2.6%), diglycerides (380 mg/kg; 2.4%), sterol esters (380 mg/kg; 2.4%), tocopherols (340 mg/kg; 2.2%), and steroid hydrocarbons (60 mg/kg; 0.4%). This information is of great use for the valorization of rice straw to obtain valuable lipophilic compounds of interest for the nutraceutical, pharmaceutical, cosmetic, and chemical industries. Moreover, this knowledge is also useful for other industrial uses of rice straw, as in pulp and papermaking, since some lipophilic compounds are at the origin of the so-called pitch deposits during pulping.